Association between controlling nutritional status score and mortality in older patients with dysphagia in Japan: a retrospective cohort study - Wang, Yan; Sun, Caihong; Tian, Xiuqing; Fan, FangFang (Frontiers in Nutrition, 2025)
BackgroundDysphagia confers elevated risks of adverse clinical outcomes. While the Controlling Nutritional Status (CONUT) score has emerged as a prognostic indicator of mortality in critically ill populations, its association with mortality risk among Japanese geriatric patients with dysphagia remains poorly characterized.ObjectiveThis retrospective cohort study investigated the prognostic utility of the Controlling Nutritional Status (CONUT) score in geriatric Japanese patients with dysphagia.MethodsClinical data from 236 consecutive dysphagia patients admitted to a tertiary care center (January 2014-January 2017) were analyzed. Nutritional risk stratification was performed using CONUT criteria. Mortality associations were assessed through multivariable Cox proportional hazards models, with subgroup analyses conducted to evaluate effect modification. Survival patterns were visualized using Kaplan-Meier methodology. A receiver operating characteristic curve analysis (ROC) was conducted to assess the predictive ability.ResultsThe cohort (median age 83 years, 59.7% female) demonstrated dose-dependent mortality relationships with CONUT severity. After full covariate adjustment, each unit CONUT increase corresponded to 15% elevated mortality risk (adjusted HR 1.15, 95% CI 1.08–1.23; P < 0.001). Graded associations were observed across nutritional risk strata vs. reference (CONUT 0–1): mild (2,3,4) HR 2.46 (1.02–5.91, P = 0.045), moderate (5,6,7,8) HR 2.91 (1.21–7.02, P = 0.017), and severe (9,10,11,12) HR 4.56 (1.84–11.3, P = 0.001). Median survival durations decreased progressively: 716 days (mild), 362 days (moderate), and 106 days (severe). Further ROC curve analysis demonstrated that CONUT (AUC 0.714, 95% CI 0.649–0.779) is an effective tool to predict mortality in older patients with dysphagia.ConclusionCONUT score independently predicts all-cause mortality in Japanese elderly with dysphagia, demonstrating monotonic risk gradients across nutritional severity categories. The absence of significant interaction effects in subgroup analyses reinforces the robustness of this association.